The E3 ubiquitin ligase CHIP mediates ubiquitination and proteasomal degradation of PRMT5 - Zhang, Huan-Tian (Biochim Biophys Acta, 2015)
Protein arginine methyltransferase 5 (PRMT5) is an important member of the protein arginine methyltransferase family that regulates many cellular processes through epigenetic control of target gene expression. Because of its overexpression in a number of human cancers and its essential role in cell proliferation, transformation, and cell cycle progression, PRMT5 has been recently proposed to function as an oncoprotein in cancer cells. However, how its expression is regulated in cancer cells remains largely unknown. We have previously demonstrated that the transcription of PRMT5 can be negatively regulated by the PKC/c-Fos signaling pathway through modulating the transcription factor NF-Y in prostate cancer cells. In the present study, we demonstrated that PRMT5 undergoes polyubiquitination, possibly through multiple lysine residues. We also identified carboxyl terminus of heat shock cognate 70-interacting protein (CHIP), an important chaperone-dependent E3 ubiquitin ligase that couples protein folding/refolding to protein degradation, as an interacting protein of PRMT5 via mass spectrometry. Their interaction was further verified by co-immuoprecipitation, GST pull-down, and bimolecular fluorescence complementation (BiFC) assay. In addition, we provided evidence that the CHIP/chaperone system is essential for the negative regulation of PRMT5 expression via K48-linked ubiquitin-dependent proteasomal degradation. Given that down-regulation of CHIP and overexpression of PRMT5 have been observed in several human cancers, our finding suggests that down-regulation of CHIP may be one of the mechanisms underlying PRMT5 overexpression in these cancers.